2015 IEEE International Conference on Bioinformatics and Biomedicine (BIBM) 2015
DOI: 10.1109/bibm.2015.7359935
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression in Varroa jacobsoni mites following a host shift to European honey bees (Apis mellifera)

Abstract: Background: Varroa mites are widely considered the biggest honey bee health problem worldwide. Until recently, Varroa jacobsoni has been found to live and reproduce only in Asian honey bee (Apis cerana) colonies, while V. destructor successfully reproduces in both A. cerana and A. mellifera colonies. However, we have identified an island population of V. jacobsoni that is highly destructive to A. mellifera, the primary species used for pollination and honey production. The ability of these populations of mites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…The differentially expressed genes (DEGs) between SrW and SwtW were identified with the DESeq R package 27 , and Benjamini-Hochberg-adjusted P-values < 0.05 were considered statistically significant 28,29 .…”
Section: Analysis Of Differential Expressionmentioning
confidence: 99%
“…The differentially expressed genes (DEGs) between SrW and SwtW were identified with the DESeq R package 27 , and Benjamini-Hochberg-adjusted P-values < 0.05 were considered statistically significant 28,29 .…”
Section: Analysis Of Differential Expressionmentioning
confidence: 99%
“…The DESeq R package was used to conduct differential expression analysis of samples (Andino et al, 2016). The FDR was controlled by Benjamini Hochberg method to correct the P-values (Benjamini and Hochberg, 1995).…”
Section: Differential Expression Analysismentioning
confidence: 99%
“…Recently there was identified that Varroa jacobsoni mites started shifting the host from A. cerana to A. mellifera. There is a difference in gene expression for the mites that reproduce on A. cerana and A. mellifera (Andino et al, 2016). This proves that the mites tests A. mellifera colonies as a potential new host and brings the danger of a new mite for A. mellifera colonies.…”
Section: Parasitic Role In the Natural Host A Ceranamentioning
confidence: 82%